Structural, Functional, and Processing Perspectives on Linguistic Island Effects - Liu, Yingtong; Winckel, Elodie; Abeillé, Anne; Hemforth, Barbara; Gibson, Edward (Annual Review of Linguistics, 2022)
Ross (1967) observed that “island” structures like “Who do you think [NP the gift from__] prompted the rumor?” or “Who did you hear [NP the statement [S that the CEO promoted__]]?” are not acceptable, despite having what seem to be plausible meanings in some contexts. Ross (1967) and Chomsky (1973) hypothesized that the source of the unacceptability is in the syntax. Here, we summarize how theories of discourse, frequency, and memory from the literature might account for such effects. We suggest that there is only one island structure—a class of coordination islands—that is best explained by a syntactic/semantic constraint. We speculate that all other island structures are likely to be explained in terms of discourse, frequency, and memory.
Keywords: syntactic islands; long-distance dependencies; filler-gap dependencies; discourse constraints; usage-based grammar; syntactic constructions; Focus–Background Conflict; linguistic interference; linguistic encoding